MANAGING CONTEMPORARY SECURITY THREATS IN THE LIGHT OF THE SYSTEMS THEORY - Case Study: COVID-19 (Security Dialogues, 2024)
The crisis that emerged from the COVID-19 epidemic represents a complex problem situation, characterized by an enormous number of various subjective and objective factors, as a result of multiple co-determination, mutual causality and variable interactions between them. Furthermore, there is a significantly high level of uncertainty, primarily based on the fact that it is about relatively new and unknown risk factors, and its initial changes led to dramatic consequences in every aspect of life on national, regional and global levels, in an extremely short time. The effect of the time “compression” and the ultimate destructive potential of the epidemic have been added to already limited possibilities in the aspect of planning and decision-making, in order to manage the crisis situation as adequately as possible. Starting with an interdisciplinary approach to resolving complex problems, by exceeding the “artificial” dichotomy between natural and social sciences, the system approach emerges as the most adequate approach for managing existing crises. Finally, the co-authorsreviewed different ways of managing crisis situation, or different strategies for exceeding crises (specifically the pragmatist approach), the potential of the short-term prognoses and predictions (with an accent on the famous scenario-planning method), including the implications of the strategic “surprises” (black swans, black elephants, or dragon kings).
Keywords: COVID-19, risk management, crisis management, systems theory, uncertainty